Incentive regulation: Evidence from German electricity networks - Michael Hellwig; Dominik Schober; Luís Cabral (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
We propose a difference-in-differences (DiD) approach to estimate the impact of incentives on cost reduction. We show theoretically, and estimate empirically, that German electricity distribution system operators (DSOs) pile up more costs in the year used to determine future prices when subject to a lower-powered regulation mechanism. The difference is particularly significant (about 10% of total cost) for firms in the upper quartile of the efficiency distribution, a pattern which is consistent with the pooling of types under the threat of ratcheting. In light of heterogeneous network reinforcement across DSOs due to local wind and solar power expansion, cost inflation will particularly hit already hard-struck DSOs' customers.
Keywords: K23; L51; L94; L98; D24; D82; 330; regulation; ratchet effect; electricity utilities; difference-in-differences; efficiency analysis